Investigating the Effectiveness of Blended Learning as a New Strategy for Teaching Anatomy to Medical Students: A Systematic Review - Zahra Karbasi; Parisa Eslami; Maryam Zahmatkeshan; Sadrieh Hajesmaeel Gohari (Kerman University of Medical Sciences, 2023)
Background: The combined use of electronic and traditional education is called blended learning. Anatomy is a major in medical education. Using this method creates flexible learning environments and more interaction in learning.Objectives: The present study was conducted to investigate the effect of blended learning on teaching anatomy to medical students.Methods: This comprehensive literature review was conducted on December 3, 2022. Our research was conducted by adhering to the PRISMA guidelines. Online databases PubMed, Eric, and Web of Science were systematically searched for relevant articles using predefined keywords. Using EndNote, all relevant literature published within the past five years was retrieved and further analyzed.Results: Our comprehensive search strategy resulted in the retrieval of 351 articles. After screening the articles and selecting the articles based on the inclusion criteria, 22 articles were eligible and included in the study. Most of the studies were conducted in India (n = 5), China (n = 2), United Kingdom (n = 2), and Portugal (n = 2). The majority of studies were conducted in 2022 (n = 7). The most important finding of all reviewed articles was the effectiveness of blended learning, which is mentioned as an effective method for teaching anatomy.Conclusion: Blended learning can improve performance and increase satisfaction and motivation in students. Identifying suitable learning resources with medical students' abilities improves learners' knowledge. Applying new learning methods can be very effective as some conditions, such as the COVID-19 crisis, limit access to corpses and physical presence.